Perfluoroalkyl substances (PFASs) in aquatic products from the Yellow-Bohai Sea coasts, China: Concentrations and profiles across species and regions. (15th June 2023) - Guo, Mengmeng; Wu, Feng; Geng, Qianqian; Wu, Haiyan; Song, Zhiling; Zheng, Guanchao; Peng, Jixing; Zhao, Xinnan; Tan, Zhijun
Abstract: Perfluoroalkyl substances (PFASs) are emerging contaminants capable of harming human health, primarily via ingesting aquatic products. The current study monitored a survey of 23 PFASs in 1049 aquatic products from the coasts of the Yellow-Bohai Sea in China to comprehensively investigate the concentrations and distributions of PFASs. PFOA, PFOS, PFNA, PFOSA, and PFUdA were more predominantly and frequently detected than other PFASs in all samples, dominating PFAS patterns in aquatic products. The mean levels of ∑PFASs in different species followed the order: marine shellfish > marine crustaceans > fish > cephalopods > sea cucumber. Profiles of PFASs differ between species, suggesting species-specific accumulation plays a role. Various aquatic species are potential environmental bioindicators that signal individual PFAS contamination. For instance, clams can act as a potential PFOA bioindicator. High ∑PFAS levels in some sites (such as Binzhou, Dongying, Cangzhou, and Weifang) could be attributed to industrial activities involving fluoropolymer manufacture. The differences between PFAS concentrations and profiles in aquatic products across the study regions have been proposed as PFAS fingerprints of the Yellow-Bohai Sea coasts. Analyses of principal components and Spearman correlations indicated that the precursor biodegradation possibly contribute to C8 –C10 PFCAs in the study samples. This study reported a wide presence of PFASs in different species of aquatic products across the Yellow-Bohai Sea coasts. The potential health risks that PFASs pose in certain species (such as marine shellfish and marine crustaceans) should not be neglected. Graphical abstract: Image 1 Highlights: PFOA, PFOS, PFOSA, PFNA and PFUdA dominated PFAS patterns in aquatic products. Different species of aquatic products have peculiar profiles. Potential bioindicators that signal individual PFAS pollution were observed. Region differences across Yellow-Bohai Sea coasts were proposed as PFAS fingerprints.